Metabolic Dysfunction Associated Steatotic Liver Disease (MASLD): A Narrative Review (Green Life Medical College Journal, 2025)
Metabolic dysfunction associated steatotic liver disease (MASLD), formerly known as NAFLD (Non-alcoholic fatty liver disease), is an emerging prevalent disease affecting millions of people worldwide. The article aims to provide a comprehensive review of epidemiology, pathophysiology, diagnostic workups, evolving management options, and outcomes. Primarily factored by insulin resistance, the disease inflammation is affected later by oxidative stress. Patients often have concomitant morbidities such as diabetes, hypertension, obstructive sleep apnea, and obesity, although MASLD itself can be asymptomatic. Liver enzymes, particularly alanine transaminases (ALT), are elevated, along with some blood markers. Diagnostic evaluation includes ultrasound imaging, non-invasive biomarkers, fibroscan, and liver biopsy. To forecast a poor prognosis, fibrosis risk stratification is necessary. The gold standard diagnostic test is liver biopsy, which is limited in use due to invasiveness. The key treatment of MASLD is weight loss by diet and exercise, which are added with limiting alcohol and regular exercise. Therapeutic interventions are yet to be established, although few medications have a narrow spectrum of action. Obese patients may undergo bariatric surgery if the criteria are matched. All the cardiometabolic risk factors should be optimized with proper interventions. Affected individuals should be monitored at regular intervals to assess any changes toward hepatic cirrhosis and carcinoma. To sum up, increasing public awareness and the scopes of scientific research are essential to combat the emerging epidemic.Green Life Med. Col. J. 2025; 10(1): 26-33